Routledge Handbook of Contemporary African Women
1 online resource (526)
Keywords: The Routledge Handbook of Contemporary African Women highlights the achievements and progress being made by African women across a wide range of sectors in society. Without glossing over the very real challenges which women in Africa continue to face, this landmark handbook demonstrates how women across the continent are deploying their agency to achieve notable progress in areas as diverse as: Pandemics Climate Change Science & Technology Entrepreneurship Higher Education Youth & Older People Challenging prevailing narratives and stereotypes about African women, this handbook provides a more positive perspective into African womens progressive actions for sustainable development. It will be an essential read for readers across the fields of gender, environment, political science, history, development studies, religious studies and African Studies.